Hypoglycemic effect and the mechanism of action of a polysaccharide from sweet corncob in a high-fat diet and streptozotocin-induced diabetic mice - Xin Wang; Weiye Xiu; Ye Han; Zhili Wang; Yu Luo; Yongqiang Ma (Food Science and Human Wellness)
Type 2 diabetes mellitus (T2DM) is a metabolic disease caused by a glycolipid metabolism disorder and islet β-cell dysfunction. SCP-80-I is a biologically active water-soluble polysaccharide isolated from sweet corncob, an agricultural byproduct. The hypoglycemic effects of SCP-80-I on T2DM mice and its mechanisms were investigated in this study. SCP-80-I was found to significantly reduce blood glucose and lipid deposition levels in T2DM mice, as well as decrease serum leptin and increase adiponectin secretion. Interestingly, real time-polymerase chain reaction (RT-PCR) and Western blotting results revealed that SCP-80-I could regulate the expression of several glycolipid metabolisms and insulin secretion genes and proteins, including 5’-AMP-activated protein kinase (AMPK), carnitine palmitoyltransferase I (CPT1), and acetyl coenzyme A carboxylase (ACC) in the liver and AMPK, sirtuin 1 (Sirt1), peroxisome proliferator-activated receptorycoactivator-1 (PGC-1α), and uncoupling protein 2 (UCP2) in the pancreas. To have a hypoglycemic effect, SCP-80-I regulated glycolipid metabolism and islet cell function in the liver by regulating the AMPK/ACC/CPT1 signaling pathway and the AMPK/Sirt1/PGC-1α and AMPK/Sirt1/UCP2 signaling pathways. These findings improve our understanding of polysaccharides derived from sweet corncob and the use of SCP-80-I in the production of hypoglycemic foods.